Liposome Encapsulated Hemoglobin Photosensitization by Protoporphyrin - A. ALFAHHAD, MARWAN (Asian Journal of Chemistry, 2010)
Liposome encapsulated hemoglobin (LEH) photosensitization by the localized protoporhyrin in the LEH membrane leads to liposome membranes damage of the liposomeencapsulated hemoglobin through out the photooxidation process of the LEH target in the visible electromagnetic wave range. The paper presents an empirical study of the photohemolysis of the LEH in the presence of protoporphyrin. In previous studies, it has been shown that the membrane damage cannot be attributed to photooxidation of unsaturated fatty acid side chains. But recent experiments showed that some amino acid residues of membrane proteins, unsaturated fatty acid side chains of phospholipids and cholesterol are sensitive to photooxidaton, induced by protoporphyrin. The significance of this paper is that cholesterol appeared to be very sensitive to protoporphyrin induces photooxidation in the LEH membrane, not the phospholipids unsaturated fatty acid side chains in the liposomes construction.